Analysis Of The Influence Of Collaborative Skills On Innovation Mediated By Work Ethic In West Sulawesi Provincial Government Office Employees - Sakaria K; Mattalatta Mattalatta; Baharuddin Baharuddin; Jamaluddin Bata Ilyas (International Journal of Social Service and Research, 2023)
The research is hoped can provide a critical analysis for improving collaborative skills to encourage the realization of innovation that is supported by maximum enthusiasm and work ethic, so the aim of this research are to test and to analyze corelation of collaborative skills on innovation through work ethic both directly and indirectly. The results of this study had found that collaborative skills have a positive and significant effect on work ethic, however collaborative skills just found a negative effect but have insignificant effect on innovation. It was also found that work ethic had a positive and significant effect on innovation, as well as collaborative skills had a positive and significant effect on innovation was found when mediated by work ethic in the West Sulawesi Province Government office. To Regional Officer Organizations should pay attention to the role of collaborative skills, particularly by encouraging the improvement of innovation services given to the community, as well as being able to apply the principles of a more optimal work ethic so that the actualization of a capable work spirit will be realized and produce excellent service. Innovation is an essential variable to improve so that the innovation of working principles will encourage more satisfying service products. Therefore, it is necessary to strengthen collaborative skills to encourage more and to grow better work innovation at West Sulawesi Province Government Office so that public services can be maximized